Sihat Secara Fitrah, Sihat Tanpa Obat: Seminar Kesehatan Holistik Bersama Dr. Hashlina Bt Rushdi di Maahad Tahfiz Arabic Al-Gontory Lil Banat Selangor Malaysia - Herlina, Herlina; Ernawati, Ernawati; Rois, Ajun; Novita, Evi; bt Rushdi, Hashlina; Laela Fitriani, Baiq; Khoirunisa, Nurul; Mariam, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The seminar entitled “Healthy by Nature, Healthy without Medicine” featured Dr. Hashlina bt Rushdi, a lecturer at the University of Malaya Foundation Program in Physics and Holistic Science, as the keynote speaker. This seminar aimed to provide a deeper understanding of holistic health concepts based on human nature (fitrah), which emphasize maintaining the balance of body and soul without reliance on chemical drugs. The seminar was conducted through presentations, interactive discussions, and a question-and-answer session. Participants, consisting of students and Islamic boarding school members, gained new insights into the importance of healthy lifestyles, stress management, natural diet, and utilizing the body’s innate potential for self-healing. The outcome showed an increased awareness among participants regarding the paradigm of living healthily in accordance with human nature, which can be applied in their daily lives.